Reproductive management and reproductive performance of dairy herds in urban and peri-urban dairy production systems in Addis Ababa milk shed - Mekasha, Yoseph; Tegegne, Azage; Yami, A.; Umunna, N.N. (Ethiopian Society of Animal Production, 2000)
A study was carried out to investigate the reproductive management and reproductive performance of dairy herds in the intensively managed urban and peri-urban dairy production systems of the Addis Ababa milk shed between September 1997 and January 1998. Fifteen dairy farms from intra-urban, 20 from secondary town and 6 from large peri-urban forming a total of 41dairy farms were used. Cross-sectional survey was implemented across the farms and data was collected on the reproductive management and reproductive performance of dairy herds in the system. The result indicated that majority of the dairy farms combine age and size as criteria to breed heifers for the first time. However, 20% of the intra-urban, 30%, of the secondary town and 17% of the large peri-urban farms allow, heifers to mate whenever they manifest heat. About 50% of the large peri urban, 45% of the secondary town and 40% of the intra urban combine Artificial insemination and natural mating. Al alone is mainly used by the large peri urban (50%), however, natural service alone is manly, used by the intra urban farms (53%). Among the farms that use AI, 67% of the large peri urban, 65% of the secondary town and 47% of the intra urban indicated that AI service is less accessible/efficient. All dairy farms visited detect estrus manually by observing the cow/s on heat. Forty seven percent of the intra urban, 35% of the secondary town and 16% of the large peri urban have no specific time for estrus detection: However, majority of the farms observe animals for heat early in the morning. Conception in the farming system is confirmed by using pregnancy diagnosis and closely watching non return. About, 80% of the intra-urban and 30% of the secondary town farms preferred to keep on waiting, while, 20% of the intra urban, 45% of the secondary town and 50% of large peri urban preferred to cull when they experience an extended calving interval. The mean age of heifers at first mating and at first calving was 20.1 (+ or -) 3.7 and 29 (+ or -) 3.5 months, respectively. The mean PPAI, calving interval and number of services per conception were 103(+ or -) 61 and 576 + or -) 216, days and 2.2 (+ or -) 0.6, respectively.